A Novel Watermarking Scheme Based on PSO Algorithm - Wang, Ziqiang; Sun, Xia; Zhang, Dexian (Bio-Inspired Computational Intelligence and Applications, 2007)
In this paper, a novel blind watermark extracting scheme using the Discrete Wavelet Transform (DWT) and Particle Swarm Optimization(PSO) algorithm is introduced. The watermark is embedded to the discrete multiwavelet transform (DMT) coefficients larger than some threshold values, and watermark extraction is efficiently performed via particle swarm optimization algorithm.The experimental results show that the proposed watermarking scheme results in an almost invisible difference between the watermarked image and the original image, and is robust to common image processing operations and JPEG lossy compression.